Efforts to Enhance Learning Motivation Using the Inquiry Method in Science Learning for 4th Grade Students at The SD Negeri 01 Ulak Karang - Antasya, Salma; Stavinibelia, Stavinibelia; Efrina, Gusnita (The Future of Education Journal, 2026)
This research was conducted because there was a problem due to low student learning motivation in class IV SDN 01 Ulak Karang and This research aims to determine the increase in students’learning motivation by using the Inquiry method in learning science chapter 5 regarding. This research is a Rustiyarso model classroom action research using the inquiry method which was carried out out in 2 cycles. The subjects in this research were 25 class students consisting of 10 male students while 15 female students. The results of the pre-action obtained before using the inquiry method saw the state of students’ learning motivation only reaching 36.72%. After using the inquiry method, there was an increase in students’ learning motivation reaching 60,18 % for cycle I of the first meeting, 69,72% for cycle I of the third meeting 71,44% for cycle I of the third meeting and 75,15% for cycle I the third meeting. The results obtained from cycle II for the first meeting were 76,76%, for the second meeting it was 77.88%, for the third meeting it was 79,46% and for the fourth meeting it was 85,04%. With the results obtained from cycle I and cycle II, there was an incease in learning motivation using the inquiry method.